The use of Nd: YAG laser for ablation of dental material - Noorsyazwani Zulkifli; Fatanah M. Suhaimi; Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Norehan Mokhtar (2015)
The effect of Nd: YAG laser pulses with a wavelength of 1064nm and 3mm of beam diameter on dental tissue enamel contains an adhesive material (transbond plus self-etching primer) is studied. Laser provides an ability to accurately deliver a large amount of energy into a confined regions. Additionally, Field Emission Scanning Microscopy (FESEM) and Energy Dispersive X-ray (EDX) are used to analyze the physical and chemical characteristics of raw teeth, teeth with an adhesive and teeth after laser irradiation. Sample was irradiated at 1.5Hz of pulse rate, 200ms of pulse width and 150J cm-2, 200J cm-2, 250J cm-2, and 300J cm-2 of energy fluence. The effects of using multiple settings of fluence are discussed. It is demonstrated that, the ablation threshold for adhesive materials are much lower than the fluence threshold laser for enamel and higher with thicker adhesive material. Besides, x-ray energy dispersive spectroscopy (EDX) analysis of enamel indicates several elements include oxygen, phosphorus, calcium, silicon, and carbon on raw teeth. Considering the thickness of the transbond plus self-etching primer and the high pulse Nd: YAG laser, it is demonstrated that the effective ablation is between 250-300J cm-2. In conclusion, Cynosure Cynergy Nd: YAG laser has high potential in removing dental adhesive material and therefore it can be used clinically